HUBUNGAN EFEKTIVITAS KERJA DAN INDIVIDUAL PERFORMANCE TERHADAP PRODUKTIVITAS KINERJA KARYAWAN DI PERUSAHAAN ASBA MINA - Elang Mulya Pratama; Henry Susanto Pranoto (Universitas Ciputra Surabaya, 2022)
Every company certainly needs employees to work for. Thus, the employees’ performance is an important aspect that help create a successful company. The employees’ performances may include discipline, working adaptation environment ability, and working effectivity. The length of working experiences will also increase working productivity of the employees. Employees’ performance productivity is the key that effects the production of goods and positively influence the effective working activities. The purposes of this research, (1) to find any significant relationship between working effectiveness of the employees and the employees’ performance productivity at AsbaM ina company, based on job satisfaction, the readiness to work, and work motivation. (2) to find any significant relationship between individual performance and working productivity of the employees at Asba Mina company. This research applies quantitative research method with a total number of 25 respondents. The correspondents result is calculated through SPSS analysis tool. All respondents are employees who still actively work at Asba Mina company. The results of this Research are : (1) working effectiveness show a significant affects on employees’ performance productivity, referring to the factors of job satisfaction, work readiness, and motivation, (2) individual performance show a significant affects on employees’ performance productivity, referring to the factor of individual performance, that is, ability, expertise, and attitude.